Strategies to integrate physiotherapists into primary health care in South Africa - Sholena Narain; Desmond Mathye (AOSIS, 2023)
Background: Health services are inaccessible in low-income countries. The National Health Insurance (NHI) bill, linked to primary health care (PHC), was introduced in South Africa to improve access to health services. Physiotherapists contribute to healthcare and improve individuals' health status across their lifespan. The South African healthcare system has many challenges: physiotherapists mostly practising at secondary and tertiary levels of care; a shortage of physiotherapists in the public health systems and rural areas; the omission of physiotherapy in health policies. Objectives: To explore strategies to integrate physiotherapy services in PHC settings in South Africa. Method: Our study used a qualitative, exploratory and descriptive approach to collect data from nine doctorate physiotherapists at South African universities. Data were thematically coded. Results: The themes are to (1) improve societal knowledge of physiotherapy, (2) ensure policy representation of the profession, (3) transform physiotherapy education, (4) broaden the role of physiotherapy, (5) eradicate professional hierarchy and (6) increase the physiotherapy workforce. Conclusion: Physiotherapy is not well known in South Africa. Physiotherapy is needed to feature in health policies to transform education focussing on disease prevention, health promotion and functioning in PHC. Broadening physiotherapy roles should consider the regulator's ethical rules. Physiotherapists should proactively collaborate with other health professionals to dismantle professional hierarchies. Without addressing the urban-rural, private-public divide, the physiotherapy workforce cannot improve, to the detriment of PHC. Clinical implication: Implementing the suggested strategies may facilitate physiotherapy integration into PHC in South Africa.